Dose‐response relationship between depressive symptoms and hospital readmission. Issue 6 (6th March 2014) - Cancino, Ramon S.; Culpepper, Larry; Sadikova, Ekaterina; Martin, Jessica; Jack, Brian W.; Mitchell, Suzanne E.
<x xml:space="preserve">Abstract</x> BACKGROUND Evidence suggests depression increases hospital readmission risk. OBJECTIVE Determine whether depressive symptoms are associated with unplanned readmission within 30 days of discharge of general medical patients. DESIGN Secondary analysis of the Project Re‐Engineered Discharge (RED) randomized controlled trials. SETTING Urban academic safety‐net hospital. PATIENTS A total of 1418 hospitalized adult English‐speaking patients. INTERVENTION The 9‐Item Patient Health Questionnaire (PHQ‐9) was used to screen patients for depressive symptoms. MEASUREMENTS Hospital readmission within 30 days of discharge. Poisson regression was used to control for confounding variables. RESULTS There were 225 (16%) patients who screened positive for mild depressive symptoms (5 ≤PHQ‐9 ≤9) and 336 (24%) for moderate or severe depressive symptoms (PHQ‐9 ≥10). After controlling for confounders, a higher rate of readmission was observed in subjects with mild depressive symptoms compared to subjects with PHQ‐9 <5, incidence rate ratio (IRR) 1.49 (95% confidence interval [CI]: 1.11‐2.00). The adjusted IRR of readmission for those with moderate‐to‐severe symptoms was 1.96 (95% CI: 1.51‐2.49) compared to those with no depression. CONCLUSIONS Screening positive for mild and moderate‐to‐severe depressive symptoms during a hospitalization on a general medical service is associated with an increased dose‐dependent readmission rate within 30 days of discharge in an urban, academic, safety‐net hospital. Further research is needed to determine whether treatments targeting the reduction of depressive symptoms reduce the risk of readmission. Journal of Hospital Medicine 2014;9:358–364. © 2014 Society of Hospital Medicine